Determinants of banks’ total factor productivity: the post-Asian financial crisis experience of the Philippines - Sufian, Fadzlan (Inderscience Enterprises Ltd., 2012)
The present paper employs the Malmquist Productivity Index (MPI)method to examine the sources of total factor productivity change of the Philippines banking sector during the period of 1998 to 2008. The empirical findings suggest that the Philippines banking sector has exhibited productivity regress due to technological regress. The results indicate that both the domestic and foreign banks have exhibited productivity regress due to technological regress rather than efficiency decline. We find that the more diversified Philippines banks tend to be less productive in their intermediation function. On the other hand, the relatively more productive Philippines banks are also the ones which are relatively more profitable. The results seem to suggest that the different structures of bank ownership have no significant impact on bank productivity.